Hubungan Penggunaan Aplikasi Google Classroom Dengan Motivasi Belajar Siswa Kelas V SDN-4 Palangka Tahun ajaran 2021/2022 - Vera Veronica; Kuswari; Asih Utami; Roso Sugiyanto (Sangkalemo : The Elementary School Teacher Education Journal, 2022)
For elementary school students, online learning can cause students' learning motivation to decrease if the learning activities are not interesting for students. One of the applications used in online learning today is Google Classroom. The google classroom application provides various features that can be used for learning activities by teachers and students and is easier to use. This research is quantitative which consists of one independent variable and one dependent variable. The research sample was the fifth grade students of SDN-4 Palangka with a total sample of 54 students. Data from the variables of the use of the google classroom application and learning motivation data were collected using a questionnaire. Furthermore, the data that has been obtained, tabulated and then analyzed using the product moment correlation formula to determine whether or not there is a relationship between research variables, then analyzed by t-test to determine whether or not the relationship is significant. The trial and the results were analyzed using the SPSS 25 program. Based on the data analysis of the results of this study, it can be seen that there is a significant relationship between the use of the google classroom application and learning motivation in fifth grade students at SDN-4 Palangka, this is evidenced by the results of the calculation of the product moment correlation. it is known that the value of r-count = 0.509 > r-table of 0.263 at an error level of 5% and the magnitude of N = 54 and the results of the calculation using the t-test, it is known that the t-count is 4.26 greater than the value of t-table = 2.00 which means that there is a significant relationship between google classroom application and learning motivation.